Mutagenic Effectiveness and Efficiency of EMS and Sodium Azide in Mungbean [Vigna radiata (L.) Wilczek] - Mahto, C. S.; Suman, Sweta; Kumar, Niraj; Sen, Shreya (International Journal of Bio-resource and Stress Management, 2018)
The present experiment assesses the relative effectiveness and efficiency of two widely used chemical mutagens on two well adapted varieties of Mungbean namely Pusa Vishal and SML-668 which was treated with 3 different doses each of EMS (0.2, 0.4, and 0.6%) and Sodium azide (0.06, 0.08, and 0.1%). The relative effectiveness and efficiency was assessed from the data on biological damage in M1 generation and frequency of chlorophyll mutants in M2 generation. The mutagenic effectiveness was inversely proportional to the increasing concentrations or doses of mutagens in Sodium azide. Low concentrations were found to be most effective and had promotary effect on plant height, pods per plant, 100 seed weight, seed yield per plant, branches per plant and pod length while both promotary and inhibitory effect were observed for seeds per pod, days to flowering and days to maturity. Sodium azide (SA) was found to be more effective mutagen to produce high frequency of chlorophyll mutations followed by EMS. It was also found that the lower concentrations of both mutagens were most effective in both the varieties. The decrease in effectiveness with increasing concentrations of mutagen could be attributed to the biological damage (like seedling injury, lethality, and sterility) which increased with increase in dose at faster rate than the mutations. Mutagenic efficiency is referred to the frequency of chlorophyll mutations in relation to M1 damage. Both the mutagens viz. EMS and Sodium azide exhibited gradual decrease in mutagenic efficiency with the increasing concentration or doses with respect to seedling injury and lethality.